P17822_Understanding the Composition and Spatial Distribution of Biological Selenate Reduction Products for Potential Selenium Recovery - Amy Marilyn Mckenna; Huan Chen (Open Science Framework, 2022)
This work was supported by a planning grant at Florida State University. Work performed at the National High Magnetic Field Laboratory ICR Facility is supported by the National Science Foundation Division of Chemistry through DMR 1644779 and the state of Florida.